Cervical cancer incidence and survival in Korea: 1993–2002. Issue 5 (1st September 2006) - Chung, H. H.; Jang, M. J.; Jung, K. W.; Won, Y. J.; Shin, H. R.; Kim, J. W.; Lee, H.-P.; ,
Abstract : This study examined the incidence rates, histologic and stage distribution, and long-term survival rates of patients with cervical cancer in Korea. A total of 44, 182 patients diagnosed with cervical cancer between 1993 and 2002 were reported to the Korea Central Cancer Registry and the Gynecologic Oncology Committee of Korean Society of Obstetrics and Gynecology. The age-standardized incidence rates were 19.0, 17.8, and 15.1 per 100, 000 women in 1993–1995, 1996–1998, and 1999–2002, respectively. The incidence rates of adenocarcinoma (AC) have been in the range between 1.2 in 1993–1995 and 1.4 in 1999–2002, while those of squamous cell carcinoma declined from 15.1 in 1993–1995 to 12.2 in 1999–2002. The 5-year relative survival rate was 79.2%. Relative survival rates, according to stage by the FIGO, at 5 years were 94.2%, 69.7%, 38.9%, and 21.1% for stages I, II, III, and IV respectively. Relative survivals improved between 1993 and 1997, probably due to the introduction of cervical cancer screening and effective treatment. The incidence rates of AC have been constant despite decreased cervical cancer in Korea. Introduction of cervical cancer screening and effective treatment may have contributed to the improved relative survival.